2011
DOI: 10.3390/molecules16075735
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity of Ixora parviflora in a Cell/Cell-Free System and in UV-Exposed Human Fibroblasts

Abstract: Polyphenols and flavonoids possess a variety of biological activities including antioxidant and anti-tumor activities. Ixora parviflora is a member of the flavonoid-rich Rubiaceae family of flowering plants and used as folk medicine in India. The aim of this study was to investigate the antioxidant activity of Ixora parviflora extract (IPE) in a cell-free system and erythrocytes, and the ability of IPE to inhibit reactive oxygen species (ROS) generation in human fibroblasts (Hs68) after ultraviolet (UV) exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 32 publications
0
37
0
1
Order By: Relevance
“…Solar radiation passes through the atmosphere and contributes to many kinds of skin disorders (Afaq et al, 2005), including immuno-suppression (Prasad and Katiyar, 2013), premature skin aging, and skin cancer (Thomas-Ahner et al, 2007). Intracellular generation of ROS such as superoxide anion, hydroxyl radical, singlet oxygen, and hydrogen peroxide results in the hazardous state of cellular oxidative stress, which is a crucial mediator of UVB-induced aging (Wen et al, 2011). At the molecular level, UVB can also induce intracellular ROS generation (Brenneisen et al, 2002), which can directly or indirectly cause oxidative damage to DNA, proteins, and lipids in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…Solar radiation passes through the atmosphere and contributes to many kinds of skin disorders (Afaq et al, 2005), including immuno-suppression (Prasad and Katiyar, 2013), premature skin aging, and skin cancer (Thomas-Ahner et al, 2007). Intracellular generation of ROS such as superoxide anion, hydroxyl radical, singlet oxygen, and hydrogen peroxide results in the hazardous state of cellular oxidative stress, which is a crucial mediator of UVB-induced aging (Wen et al, 2011). At the molecular level, UVB can also induce intracellular ROS generation (Brenneisen et al, 2002), which can directly or indirectly cause oxidative damage to DNA, proteins, and lipids in the skin.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of Neonauclea reticulata extract to scavenge H 2 O 2 was determined spectrophotometrically as previously described [12]. Briefly, a 20 mM solution of H 2 O 2 was prepared in PBS (pH 7.4), added to various concentrations of Neonauclea reticulata extract that had been dissolved in methanol (50 to 2000  μ g/mL), and then allowed to stand at room temperature in the dark.…”
Section: Methodsmentioning
confidence: 99%
“…This assay is based on the use of an established nonfluorescent (DCFDA)/fluorescent (DCF) system that measures the levels of ROS, which are in turn responsible for the generation of fluorescence [12]. Hs68 cells were seeded in a 24-well plate at a density of 10 5 cells/well for 24 h, rinsed once with 0.5 mL PBS, and then exposed to UVB irradiation (302 nm, CL-1000 M, UVP, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Previous investigations led to the isolation of many compounds including phenolics, peptides, terpenoids and sterols from plants of the genus (Ragasa et al 2004;Idowu et al 2010;Lee et al 2010;Ikram et al 2013). Pharmacological studies showed that extracts of the genus and the isolated compounds displayed extensive activities, such as antitumour, chemoprotective and antioxidant activities (Latha & Panikkar 1998;Wen et al 2011;Wickramasinghe et al 2014). But there was no report on Ixora amplexicaulis, which is a small shrub endemic to China.…”
Section: Introductionmentioning
confidence: 98%